Institutional barriers for the implementation of climate change adaptation actions in the Mexican coastal zones - Muñoz, Norma Patricia (My University, 2018)
This paper has as its object of study the coastal and marine areas of Mexico; specifically, it focuses on the analysis of existing barriers for the implementation of actions tending to the adaptation to climate change of these fragile and dynamic regions of the national territory. The study makes a general review of the main meetings, agreements and international entities related to the global climate that have served as the basis for the XXI Conference of the Parties, from which emanated the "Paris Agreement". After analyzing some implications of the aforementioned agreement and presenting evidence of the current situation, the main legal and normative instruments of the national marine and coastal areas are reviewed; the main risks in these areas of the national territory associated with climate change are evaluated; the main existing adaptation measures are analyzed; and, the most important socioeconomic and political barriers that exist for their correct implementation are established. Finally, some lines of action are proposed to improve the current vulnerability of the coastal areas and increase their resilience.
Keywords: Cambio climático; Acuerdos; Cambio global